2018
DOI: 10.1039/c7cp08235e
|View full text |Cite
|
Sign up to set email alerts
|

UV-induced long-lived decays in solvated pyrimidine nucleosides resolved at the MS-CASPT2/MM level

Abstract: The most relevant 'dark' electronic excited states in DNA/RNA pyrimidine nucleosides are mapped in water employing hybrid MS-CASPT2/MM optimisations with explicit solvation and including the sugar. Conical intersections (CIs) between initially accessed bright ππ* and the lowest energy darknπ* excited states, involving the lone pair localised on the oxygen and/or nitrogen atoms are characterised. They are found in the vicinities of the Franck-Condon (FC) region and are shown to facilitate non-adiabatic populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
115
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(140 citation statements)
references
References 102 publications
22
115
3
Order By: Relevance
“…Geometrically similar S 1 (n O p*) minima were also reported for the keto tautomers of C, G and isoC. 24,[45][46][47]50,70 However, surface-hopping nonadiabatic molecular dynamics simulations executed for G showed that this local minimum is sampled by sparse trajectories and the prevalent photodeactivation channel drives keto-G towards the pp*/S 0 conical intersection. 70 Our direct optimization of the S 1 minimum of keto-G initiated from the S 0 geometry also did not stabilize the n O p* state, whereas the same optimization procedure returned the S 1 (n O p*) minima for both of the studied keto tautomers of isoG.…”
Section: Vertical Excitation Energies and Uv-vis Spectrasupporting
confidence: 69%
See 1 more Smart Citation
“…Geometrically similar S 1 (n O p*) minima were also reported for the keto tautomers of C, G and isoC. 24,[45][46][47]50,70 However, surface-hopping nonadiabatic molecular dynamics simulations executed for G showed that this local minimum is sampled by sparse trajectories and the prevalent photodeactivation channel drives keto-G towards the pp*/S 0 conical intersection. 70 Our direct optimization of the S 1 minimum of keto-G initiated from the S 0 geometry also did not stabilize the n O p* state, whereas the same optimization procedure returned the S 1 (n O p*) minima for both of the studied keto tautomers of isoG.…”
Section: Vertical Excitation Energies and Uv-vis Spectrasupporting
confidence: 69%
“…We also performed surface-hopping nonadiabatic molecular dynamics simulations 44 for two of the enol tautomers of isoG using the ADC(2) method for electronic structure calculations. Our results indicate that keto tautomers of isoG exhibit excited state properties similar to the keto form of cytosine, which are determined by a long lived np* excitation, [45][46][47][48][49][50] while the enol tautomers are characterized by more efficient photorelaxation mechanisms dominated by the lowest-lying singlet pp* states.…”
Section: Introductionmentioning
confidence: 99%
“…The characterised cationic ground (D 0 ) and excited (D 1 ) state minima, as well as the different low-lying conical intersections (CIs) were also optimised at the CASPT2 level of theory to establish the role of dynamic electron correlation on the geometrical parameters in these cations, as it has been shown to significantly impact the singlet manifold. [42][43][44][45] CASPT2 minima and CI optimisations (using the projection method of Bearpark et al 46 ) were also carried out with analytical gradients [47][48][49] and couplings 50 as implemented in BAGEL 51 to ensure that those obtained using numerical differentiation are correct. Linear interpolations in internal coordinates were performed between the key structures optimised (minima and conical intersections) in order to rule out the presence of potential energy barriers.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Additionally,t he photophysics of individual thymine and cytosine derivatives are still the topic of current research (e.g.,s ee refs. [26][27][28][29][30]), building the foundation for ad etailed understanding of photoreactions in the corresponding dipyrimidines.…”
Section: Introductionmentioning
confidence: 99%